Polyimide Derived from the Diels-Alder Polymerization ofDifurylmethane with N,N'- bismaleimido-4,4'-diphenylmethane - Ahmad, Jamil; A.A. Ddamba, Wilfred; K. Mathokgwane, Perez (Asian Journal of Chemistry, 2010)
Difurylmethane was synthesized and polymerized with N,N´-bismaleimido-4,4´-diphenylmethane via the Diels-Alder polycycloaddition reaction to form a polyadduct which was soluble in DMSO, acetone and methylene chloride. FTIR and solution 1H NMR data from the 2 : 1 difurylmethane-N,N´-bismaleimido-4,4´-diphenylmethane model Diels-Alder adduct prepared, facilitated the assignment of spectral features of the polyadduct. Upon treatment of the homogeneous solution of the polyadduct in methylene chloride with borontrifluoride diethyletherate at ambient temperature, aromatization of the bicyclic Diels-Alder adduct moieties in the polyadduct chains occurred resulting in the formation of an insoluble, thermally stable polyimide. Whereas the 2 : 1 difurylmethane-N,N´-bismaleimido-4,4´-diphenylmethane model Diels-Alder adduct and the polyadduct underwent 100% retro-Diels-Alder reaction in the temperature range 115–230ºC, the polyimide was stable up to about 420ºC in a N2 atmosphere, forming a high char yield of 40% at 800ºC.